Economic Trends and Macroeconomic Management In Indonesia: 1960s-1980s - Argamaya, Argamaya (Business and Management Review, 2012)
Tulisan ini membahas mengenai mekanisme penggerak ekonomi makro di Indonesia selama dua periode yakni periode 1960-1965 yang merupakan tahun-tahun yang berbahaya bagi Indonesia dan periode 1966-1989 yang merupakan tahun-tahun keberuntungan bagi perekonomian Indonesia. Indikator utama ekonomi makro menunjukkan kinerja yang mengesankan selama tahun-tahunter sebut. Penyesuaian dalam ekonomi makro memainkan peranan penting dalam menangani situasi yang kacau yang terjadi pada awal periode 1966-1989 serta goncangan baik internal maupun eksternal. Sistem dan pengawasan keuangan yang buruk serta masalah informasi asimetris, seperti kebijakan industri yang bias, kapitalisme, dan memuncaknya pinjaman cepat yang beresiko. Masalah pasar keuangan dan respon yang kurang tanggap membuat Indonesia rentan terhadap goncangan yang akan berdampak negatif pada sentimen pasar terhadap Negara. Kata Kunci: manajemen makroekonomi, pendapatan nasional, inflasi, money supply, kebijakan fiscal, kebijakan moneter, nilai tukar mata uang. This paper discusses the mechanisms of macro-economic drivers in Indonesia during the two periods; the period 1960-1965 which is a dangerous years for Indonesia and the period 1966-1989 which isa miracle years for the Indonesian economy. The main macroeconomic indicators showed an impressive performance over the years. Adjustments in macroeconomic plays an important role in dealing with the chaotic situation that occurred at the beginning of the period 1966-1989 as well as both internal and external shocks. Poor financial system and poor supervision and asymmetric information problems, such as industrial policy bias, capitalism, and rising up risky loans. Financial market issues and less-responsive responses madeIndonesia vulnerable to shocks that would bring a negative impact on market sentiment against the State. Keyword: macroeconomic management, capital income, inflation, money supply, fiscal policy, monetary policy, exchange rate.REFERENCES Ahmed, Sadiq, and Ajay Chhibber 1989. How Can Indonesia Maintain Creditworthiness and Noninflationary Growth?, World Bank Working Paper 291, World Bank, Washington, D.C. Ahmed, Sadiq, 1989. Indonesia: external shocks, policy response and adjustment performance, World Bank Report IDP 3a, World Bank, Washington, D.C. Ahmed, Sadiq, and Basant K. Kapur, 1990. How Indonesia's Monetary Policy Affects Key Variables', World Bank Working Paper 349, World Bank, Washington, D.C. Ahmed, Sadiq, 1993. Appropriate Macroeconomic Management in Indonesia's Open Economy, World Bank Discussion Paper 91, World Bank, Washington, D.C. Asian Development Bank, 2001. Corporate Governance and Finance in East Asia, ADB Publications, Manila.  Azis, Iwan J., 1999. `Exchange rate, capital flows and reform sequencing in Indonesia: policy trend and CGE model application', in J. de Brun and R. Luders (eds.), Macroeconomic Policy and the Exchange Rate, International Centre for Growth, San Francisco, CA. Azis, Iwan J., and ArieKuncoro, 2000. From standard approach to an economy-wide model of total factor productivity, Conference of the Impact of Hi-Tech on the Economy, Kuala Lumpur, Malaysia, September 11. Barichello, Richard R., and Frank R. Flatters, 1991. ‘Trade policy reform in Indonesia’, in Dwight H. Perkins and Michael Roemer (eds), Reforming Economic Systems in Developing Countries, Harvard University Press, MA.Bernanke, Ben S. and Alan S. Blinder, 1988. `Is it money or credit, or both, or neither? credit, money, and aggregate demand', American Economic Review, 78(2):435-439. Bernanke, Ben S. and Mark Gertler, 1989. `Agency costs, net worth, and business fluctuations', American Economic Review, 79(1):14-31. Bernanke, Ben S. and Mark Gertler, 1990. `Financial fragility and economic performance', Quarterly Journal of Economics, 105(1):87-114. Bernanke, Ben S. and Mark Gertler, 1995. `Inside the black box: the credit channel of monetary policy transmission', Journal of Economic Perspectives, 4(9):27-48. Booth, A., 1989. `Indonesia's agricultural development in comparative perspective', World Development, 17(8):1235-1254. Calvo, Guillermo A., Leonardo Leiderman, and Carmen M. Reinhart, 1994a.`The capital inflows problem: concepts and issues', Contemporary Economic Policy, 12:54-66. Calvo, Guillermo A., Leonardo Leiderman, and Carmen M. Reinhart, 1994b. `Capital inflows to Latin America: the 1970s and 1908s', in Edmar L. Bacha (ed.), Economics in a Changing World: development, trade, and the environment', Mcmillan, London. Calvo, Guillermo A., Leonardo Leiderman, and Carmen M. Reinhart, 1996. `Inflows to developing countries in the 1990s', Journal of Economic Perpectives, 10(2):123-39. Calvo, Guillermo A., 2001. `Economic policy in stormy waters: financial vulnerability in emerging economies', Journal of Applied Economics, 1:1-15. Campos J. Edgardo and Hilton L. Root, 1996. The Key to the Asian Miracle: making shared growth credible, Brookings Institute, Washington,D.C. Cardoso, Eliana A., and RudigerDornbusch, 1995. `Foreign private capital flows', in J. Behrman and T. Srinivasan (ed.), Handbook of Development Economics , North Holland. Chuhan, Punam, StijnClaessens, and NlanduMamingi, 1998. `Equity and bond flows to Latin America and Asia: the role of global and country factors', Journal of Development Economics, 55(2):441-465. Claessens, Stijn, Simeon Djankov and Larry H.P. Lang, 1998. East Asian Corporates: growth, financing and risks over the last decade, World Bank, Washington, DC. Claessens, Stijn, Simeon Djankov and Larry H.P. Lang, 1999. Who Controls East Asian Corporations?, Policy Research Working Paper 2054, World Bank, Washington, D.C. Claessens, Stijn, Simeon Djankov and Larry H.P. Lang, 2000. `The separation of ownership and control in East Asia corporations', Journal of Financial Economics, 58(1-2):81-112. Corbo, Vittorio and Leonardo Hernandez, 1996. `Macroeconomic adjustment to capital inflows: lessons from recent Latin American and East Asian experience', World Bank Research Observer, 11(1):61-85. Corden, Max W., 1984. `Booming sector and Dutch disease economies', Oxford Economic Papers, 36:350-380. Corden, W. Max, 1996. Pragmatic Orthodoxy: macroeconomic policies in seven East Asia economies, Occasional Paper 61, International Center for Economic Growth, San Francisco, CA. Corsetti, Giancarlo, Paolo Pesenti, and NourielRoubini, 1999. `What caused the Asian currency and Financial crisis?', Japan and the World Economy, 11:305-373. Dekle, Robert, and MahmoodPradhan, 1999.`Financial liberalization and money demand in the ASEAN countries', International Journal of Finance and Economics, 4:205-215. Douglas W. Diamond, Philip H. Dybvig, 1983. `Bank runs, deposit insurance, and liquidity', Journal of Political Economy, 91(3):401-419. Fane, George, 1999. `Indonesian economy policies and performance, 1960-98', World Economy, 22(5): 651-668. Fane, George, and Timothy Condon, 1996. `Trade reform in Indonesia, 1987-1995', Bulletin of Indonesia Economic Studies, 32(3):33-54. Fernandez-Arias, Eduardo, 1994. The New Wave of Private Capital Inflows, Policy Research Working Paper 1312, World Bank, Washington, D.C. Fernandez-Arias, Eduardo and Peter J. Montiel, 1995. The Surge in Capital Inflows to Developing Countries, Policy Research Working Paper 1473, World Bank, Washington, D.C. Ghosh, Swati, and Mari Pangestu, 1999. Indonesia: Macro-financial Linkages and Build of Vulnerabilities, ADB-World Bank Study. Gourinchas, Pierre-Olivier, Rodrigo Valdes and Oscar Landerretche, 2001. Lending booms: Latin America and the world, Economia, 1(2): 47-99. Hanna, Donald D., 1994. Indonesian Experience with Financial Sector Reform, World Bank Discussion Paper 237. Haque, NadeenUl, Donald Mathieson, and Sunil Sharma, 1996. Capital inflows to developing and transition countries: identifying causes and formulating appropriate policy responses, in IMF, 1996. World Economic Outlook, IMF Publication, Washington, D.C. Heller, Peter S., 1997, Fiscal Policy Management in an Open Capital Regime, IMF Working Paper 20, Washington, D.C. Hernandez, Leonardo and Oscar Landerretche, 1999. `Capital flows, credit booms and macroeconomic vulnerability: international experience', Money Affairs, 12(1): 1-36. Hill, Hal, 1994. `ASEAN economic development: an analytical survey – the state of the field', Journal of Asian Studies, 53(3): 832-866. Hill, Hal, 1995. The Indonesian Economy Since 1966: Southeast Asia's Emerging Giant, Cambridge University Press, UK. Hill, Hal, 1996. Indonesia's industrial policy and performance: "orthodoxy" vindicated, Economic Development and Cultural Change, 45(1):147-174 Hill, Hal, 2000. `Indonesia: the strange and sudden death of a tiger economy', Oxford Development Studies, 28(2): 117-139. Hill, Hal (ed.), 2002. The Economic Development of South East Asia, Volume I-IV, Edward Elgar, UK. International Monetary Funds, International Financial Statistics, various issues. Kaminsky, G. L. and Reinhart, C.M., 1999.`The twin crises: the causes of banking and balance-of-payments problems', American Economic Review, 89(3): 473-500. Kenward, Lloyd R., 1999. `Assessing vulnerability to financial crisis: evidence from Indonesia', Bulletin of Indonesia Economic Studies, 35(3):71-95. Khan, Mohsin S., and Carmen M. Reinhart (eds.), 1995, Capital inflows in the APEC region, IMF Occasional Paper 122, Washington D.C. Kim, Yoonbai, 2000. ``Causes of capital flows in developing countries', Journal of International Money and Finance, 19(2): 235-253. Koenig, Linda M, 1996. Capital inflows and policy responses in the ASEAN region, IMF Working Paper 25, Washington D.C. La Porta, Rafael, Florencio Lopez-de-Silanes, Andrei Shleifer, and Robert W. Vishny, 1998, `Law and finance', Journal of Political Economy, 106(6): 1113-1155. La Porta, Rafael, Florencio Lopez-de-Silanes, Andrei Shleifer, and Robert W. Vishny, 2000. `Investor protection and corporate governance', Journal of Financial Economics, 58(1-2): 3-27. Little, Ian M. D., Richard N. Cooper, W. Max Corden, and SarathRajapatirana, 1996. Boom, Crisis, and Adjustment: the macroeconomic experience of developing countries, Oxford University Press, Washington, DC. Manning, Chris, 1999. Poverty Decline and Labour Market Change in Indonesia Lessons From the Suharto Era, Development Studies Papers, RSPAS, Canberra. Mathieson, Donald and L. Rojas-Suarez, 1993, Liberalization of the Capital Account: experiences and issues , IMF Occasional Paper 103, Washington, D.C. McCawley, Peter, 1978. `Some consequences of the Pertamina crisis in Indonesia', Journal of South East Asian Studies, 9(1):1-27. McLeod, Ross H., 1997. `Explaining chronic inflation in Indonesia', Journal of Development Studies, 33(3):392-410. McLeod, Ross H., 1999. `Control and competition: banking deregulation and re-regulation in Indonesia', Journal of the Asia Pacific Economy, 4(2):258-297. McKinnon, Ronald I. and Huw Pill, 1999. `Exchange-rate regimes for emerging markets: moral hazard and international overborrowing', Oxford Review of Economic Policy, 15(3): 19-38 Mello, Luiz R. De and Kiichiro Fukasaku, 2000.`Trade and foreign direct investment in Latin America and Southeast Asia: temporal causality analysis', Journal of International Development, 12:903-924. Mishkin, Frederic S., 1991. Anatomy of Financial Crisis, NBER Working Paper No. 3934. Montgomery, John, 1997. The Indonesian Financial System: its contribution to economic performance, and key policy issues, IMF Working Paper 45. Montiel, Peter J., 1994. `Capital Mobility in Developing Countries: Some Measurement Issues and Empirical Estimates', The World Bank Economic Review, 8(3):311-350. Nasution, Anwar, 2000. `The meltdown of the Indonesian economy: causes, responses and lessons', ASEAN Economic Bulletin, 17(2):148-162. Paauw, D., 1977. Exchange Rate Policy and Non-extractive Exports, Core Group on Employment Strategy Discussion Paper 18. Prema-chandra, Athukorala and Peter G. Warr, 2002. `Vulnerability to a currency crisis: lessons from the Asian experience', World Economy, 25(1): 33-57. Obstfeld, Maurice, 1994. `International capital mobility in the 1990s', in P. Kenen (ed.), Understanding Interdependence: the macroeconomics of open economy, Princeton University Press. Obstfeld, Maurice, 1998. `The global capital market: benefactor or menace?', Journal of Economic Perspectives, 12(4): 9-30. Obstfeld, Maurice and Alan M. Taylor, 1998. `The great depression as a watershed: international capital mobility over the long run', in Michael D. Bordo, Claudia D. Goldin, and Eugene N. White (eds.), The Defining: the great depression and the American economy in the twentieth century, Chicago, University of Chicago Press. Reinhart, Carmen M., and Vincent.R.Reinhart, 1998. `Some lessons for policy makers dealing with the mixed blessing of capital inflows', in M. Kahler (ed), Capital Flows and Financial Crises, Cornell University Press, New York. Sachs, Jeffery, Aaron Tornell, and Andreas Velasco, 1996. `Financial crises in emerging markets: the lessons from 1995', Brookings Papers on Economic Activity, 27(1):147-199. Sato, Yuri, 1993. `The Salim group in Indonesia: the development and behavior of the largest conglomerate in South East Asia', Developing Economies, 31(4):408-441. Siregar, Reza Y., 1999. `Real exchange rate targeting and inflation in Indonesia: theory and empirical evidence', Applied Financial Economics, 9:329-336.Smith, Bruce D., 2001\textbf{. `Banks, short-term debt and financial crises: theory, policy implications, and applications A comment', Carnegie-Rochester Conference Series on Public Policy, 54(1):73-83. Usui, Norio, 1997. `Dutch disease and policy adjustments to the oil boom: a comparative study in Indonesia and Mexico', Resource Policy, 23(4):151-162. Van Wijnbergen, Sweder, 1984. `The `Dutch disease': a disease after all?', Economic Journal, 94(373): 41-55. Warr, Peter G., 1986. `Indonesia's other Dutch disease: economic effects of the petroleum boom', J.P. Neary and S. van Wijnbergen (eds), Natural Resources and the Macroeconomy, Basil Blackwell, Oxford. Warr, Peter G., 1994. `Indonesia's adjustment to petroleum boom and busts: lesson for Colombia', Conference on Lessons from Indonesia for Colombia on Managing Sudden Increases in Petroleum Revenues, Bogota, March 24-25. Woo, Wing.T., Bruce Glassburner, and Anwar Nasution, 1994. Macroeconomic Policies, Crises, and Long-term Growth in Indonesia: 1960-1990, World Bank, Washington, DC. World Bank, 1968.Economic Development of Indonesia, Washington, DC. World Bank, 1993.The East Asia Miracle, Economic Growth and Public Policy, Oxford University Press, Washington, DC. World Bank, 1996.Indonesia Dimension of Growth, Country Report 15383-IND, Washington, DC. World Bank, 1997. Private Capital Flows to Developing Countries: the road to financial integration, Oxford University Press, Washington, DC.